Barriers and enablers to postpartum depression and anxiety screening: A qualitative study of Victorian maternal and child health nurses' practices. (4th August 2022) - Arefadib, Noushin; Cooklin, Amanda; Shafiei, Touran
Abstract: In Victoria, Australia, Maternal and Child Health nurses (MCHNs) play a key role in facilitating the timely identification of Postnatal Depression and Anxiety (PNDA). Understanding MCHNs' screening practices, and the factors which impact them, is central to ensuring that future screening policy agendas are evidence‐based and able to support MCHNs in carrying out this critical work. Yet, little is known about this subject. The purpose of this study was to gain an in‐depth understanding of MCHNs' screening practices, and the factors which impact them. Qualitative descriptive design with semi‐structured interviews were used. Participants were MCHNs who had been practicing for a minimum of 6 months and regularly saw new mothers. Purposeful sampling was used to facilitate diversity across participant characteristics. Twelve MCHNs were interviewed between March and May 2021. Thematic analysis was conducted to identify patterns across our data. Qualitative content analysis was then used to identify issues which were most emphasised by MCHNs. Two themes were identified. Theme one, 'variations in screening practices', pertained to MCHNs' various screening practices (i.e., who, when, how) and the factors which influence them. Theme two, 'systemic barriers hinder equitable screening', pertained to factors which hindered equitable screening practices. Results indicate that systemic barriers contribute to inconsistent and inequitable screening practices, with women from culturally and linguistically diverse backgrounds less likely to be screened in line with best practice. Our findings emphasise an urgent need for MCHNs to be allocated with the resources required to screen all women equally, regardless of their cultural background.